Marine Biofilm effect on mortar surface layer. Issue 1 (1st July 2022) - Georges, M; Bourguiba, A; Maestracci, B; Gascoin, S; Goux, D; Chateigner, D; Boutouil, M
Abstract: The objective of this study is to evaluate the effect of biofilm development on the surface layer of a mortar. This work aims at understanding the modifications occurred within the cementitious matrix such as its composition as its microstructure following the bio-colonization. These properties were studied after 360 days of immersion in two immersion media (Artificial Seawater (AS) and Natural Seawater (NS)) using ATG/DTG, XRD analyses and SEM observations. It was found that the biofilm caused the dissolution of the portlandite deeper than when the mortar was not colonized (AS medium). Moreover, a strong carbonation was observed in the first millimeters of the matrix. Two polymorphs of calcium carbonate were particularly identified. Aragonite is the dominant form present on the surface of the mortar immersed in NS. Calcite and magnesian calcite were also observed but after bio-colonization of the mortar. Thus, the development and the biological activity of the biofilm seems to modify the properties of the mortar and could control the precipitation of calcium carbonates on its surface.